Epidemiologi Kejadian Luar Biasa Malaria Bulan September-November 2024: Studi Serial Kasus di Kabupaten Indragiri Hilir, Provinsi Riau - Rajunitrigo, Rajunitrigo; Muryanto, Irwan; Mahkota, Renti; Armen, Fadhil; Nuryanti, Yusni; Rizal, Fahrul; Adwiyah, Rabiatul (UI Scholars Hub, 2025)
Abstract Malaria remains a public health issue in Indragiri Hilir Regency, Riau, despite its elimination certification 2018. In 2024, a malaria outbreak occurred, and an epidemiological investigation was then carried out. This study aims to describe the epidemiological characteristics of the malaria outbreak based on person, time, and place. This study used a serial case design, analyzing all confirmed malaria cases reported in the e-SISMAL system of Indragiri Hilir Regency from September 1st to November 30th, 2024. Data on Anopheles Sundaicus habitats were obtained from epidemiological investigation reports. Univariate and bivariate analyses were conducted using the chi-square test. Among them 248 identified cases, with 50% aged 15–45 years, 55.2% male, and 27.0% housewives. Among them, 90.3% had no history of malaria, 91.5% were infected with Plasmodium vivax, and 63.7% experienced fever and/or chills. The peak of cases occurred in week 41, with 66.5% seeking treatment within 1–3 days. A total of 98.4% of cases were from Kuala Selat Village, with an Annual Parasite Incidence (API) of 112.4‰. The primary habitat of Anopheles Sundaicus was in lagoons, with the highest larval density found in water bodies with salinity level of 6–11‰. Bivariate analysis showed a significant association between male gender and high-risk occupations with symptomatic malaria status (pAnopheles Sundaicus habitats are necessary. Additional, protection for high-risk groups, education, and enhanced surveillance should be reinforced to prevent future case surges. Keywords: Malaria Outbreak, Malaria Epidemiology, Plasmodium vivax, Anopheles Sundaicus, Indragiri Hilir Regency